2022
DOI: 10.3389/fpsyg.2022.979037
|View full text |Cite
|
Sign up to set email alerts
|

Mental health self-efficacy as a moderator between the relationship of emotional exhaustion and knowledge hiding: Evidence from music educational students

Abstract: The knowledge and skills of employees could play a valuable role in organizational success. Organizations seek practices to create a knowledge-sharing culture to take full advantage of individual competencies. However, the knowledge-hiding behavior of individuals is a hurdle in the internal dissemination of knowledge and expertise. It becomes more critical in the case of teaching institutions, where the students are taught and trained. Scholars are now putting their efforts into seeking the antecedents and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…In the literature, Bandura (1977) emphasized that fear and avoidance behaviors are at lower levels in individuals with high self-efficacy and that individuals act confidently. Yıldırım (2015) stated that there is a negative relationship between individuals' self-efficacy perceptions and professional burnout, Yurt (2022) stated that self-efficacy negatively affects burnout, Zhou (2022) stated that self-efficacy negatively affects the relationship between emotional exhaustion and information retention and Dolu et al . (2023) emphasized that professional burnout can increase emotional burnout.…”
Section: Discussion (Evaluation According To National and Internation...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, Bandura (1977) emphasized that fear and avoidance behaviors are at lower levels in individuals with high self-efficacy and that individuals act confidently. Yıldırım (2015) stated that there is a negative relationship between individuals' self-efficacy perceptions and professional burnout, Yurt (2022) stated that self-efficacy negatively affects burnout, Zhou (2022) stated that self-efficacy negatively affects the relationship between emotional exhaustion and information retention and Dolu et al . (2023) emphasized that professional burnout can increase emotional burnout.…”
Section: Discussion (Evaluation According To National and Internation...mentioning
confidence: 99%
“…Studies in similar and different fields in the literature were examined, and hypotheses regarding the variables were developed. In addition to the research stated in the theoretical part of the research; Yıldırım (2015) revealed that there is a negative relationship between individuals' self-efficacy perceptions and professional burnout, Yurt (2022) revealed that self-efficacy negatively affects burnout and Zhou (2022) revealed that self-efficacy negatively affects the relationship between emotional exhaustion and information retention. Taking into account the research results, the H1 hypothesis was developed.…”
Section: Methodsmentioning
confidence: 99%
“…and greater pain tolerance [58][59][60]. Where individuals with depressive symptomology are assessed to be at risk for addictive SMU, a focused psychological intervention designed to target the elevation of their sense of control and self-efficacy may produce an analgesic effect and diminish depressive symptoms; however, this contention should be definitively tested within the context of a rigorous randomized controlled trial.…”
Section: Plos Onementioning
confidence: 99%
“…In addition, knowledge collection has an independent mediating role. Zhou (2022) empirically investigated 310 music-learning students from various universities using sampling techniques and data collected through a structured questionnaire method. Guo (2022) tested a model of factors influencing the knowledge-sharing behavior of online community members using PLS-SEM.…”
Section: Effects Of Knowledge-sharing Behavior On Group Performancementioning
confidence: 99%